Pemanfaatan Media Audio Visual Gerak dalam Pembelajaran Pemahaman Lintas Budaya - ., Selvia (Zenit, 2014)
The development of science and technology has stimulated a more innovative way in the process of learning. Learning media are supporting components in the learning process. Appropriatelearning media will assist the effectiveness of knowledge sharing process and the achievement of learning objectivity. With the advancement of technology and the availability of innovative learning media, the process of experiencing other cultural values will be much easier. By using more interactive learning media, such as audio visual motion media, the process of cross cultural understanding will no longer be limited to senses, space and time. They not only assist learners tounderstand the learning material, but also arouse the motivation and passion of the learners.Keywords: audio visual motion media, innovative, cross cultural understanding